Videogames and Post-Colonialism: Empire Plays Back - Mukherjee, Souvik (Palgrave MacMillan, 2017)
This book focuses on the almost entirely neglected treatment of empire and colonialism in videogames. From its inception in the nineties, Game Studies has kept away from these issues despite the early popularity of videogame franchises such as Civilization and Age of Empire. This book examines the complex ways in which some videogames construct conceptions of spatiality, political systems, ethics and society that are often deeply imbued with colonialism. Moving beyond questions pertaining to European and American gaming cultures, this book addresses issues that relate to a global audience ? including, especially, the millions who play videogames in the formerly colonised countries, seeking to make a timely intervention by creating a larger awareness of global cultural issues in videogame research. Addressing a major gap in Game Studies research, this book will connect to discourses of post-colonial theory at large and thereby, provide another entry-point for this new medium of digital communication into larger Humanities discourses.
Section: ix, 121 pages : illustrations ; 22 cm.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Video Games and Storytelling: Reading Games and Playing Books - Mukherjee, Souvik (Palgrave Macmillan, 2018)
The potential of video games as storytelling media and the deep involvement that players feel when they are part of the story needs to be analysed vis-a-vis other narrative media. This book underscores the importance of video games as narratives and offers a framework for analysing the many-ended stories that often redefine real and virtual lives.
OCLC: 1040048516
Keywords: 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Re-membering and Dismembering: Memory and the (Re)Creation of Identities in Videogames - Mukherjee, Souvik (Sessões do Imaginário, 2017)
The Prince of Persia in Prince of Persia: The Sands of Time (Ubisoft 2003) is ever reluctant to accept an ignominious end to his story, whether after a fall from atop a tower or after being killed by the sand demons. Every time he fails, the Prince exclaims ‘no no, that is not how it happened at all’. Like the videogame player controlling his avatar, the Prince wants the game sequence to be reloaded and replayed; only he appeals to an entity that the player often does not notice – memory. The Prince justifies the reload because he does not remember the events as they happen and he hankers for a return to a ‘true’ memory. There is an implicit problem here, however. We cannot ask the Prince what he remembers and during the game the player ends up remembering the ‘false’ memories, albeit often unconsciously. To progress further in the game, the player needs to have learned from his mistakes or, in other words, to have remembered the previous iterations of gameplay. According to the Prince’s memory, these failed instances of gameplay never happened; yet they happened in the gameplay and are remembered by players. Often, many players share the same experience and this exists as a shared memory. Players might also be drawing on collectively recorded memories – the written step by step guidelines in a walkthrough and the comments left by players on various gaming forums or wikis. What the player remembers is also often influential in determining the in-game identity of the player. Videogames themselves, such as Assassin’s Creed (Ubisoft 2008) and STALKER: Shadow of Chernobyl (GSC Gameworld 2007) have started self-reflexively exploring memory in their plots. Therefore, it will be useful to move the study of memory in videogames out of its relative obscurity and explore its multi-layered complexity.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

The Playing Fields of Empire: Empire and Spatiality in Video Games - Mukherjee, Souvik (Journal of Gaming & Virtual Worlds, 2015)
As in historical accounts, empire in video games too is concerned with the acquisition of geographical space. Like the splash of red marking the stretch of the British Empire on Victorian world maps, video games that let one play at empire are also obsessed with stamping the imperialist authority of ‘your’ nation on their in-game maps. Video game empires too work on the necessary logic of spatial expansion connected with which is the necessity to remove the ‘fog’ which prevents the player’s ‘line of sight’ from accessing information about surrounding areas. The focus on cartography and surveying in British Raj India is a useful comparison. Although much scholarship exists around the representations of the spatiality of Empire in more traditional media, there is little that addresses the video game representations of Empire. This article is about the representation and experience of space in conceptions of Empire vis-à-vis in empire-building video games, as understood in terms of both cartography and the lived experience of space. It argues that although empire-building video games are largely framed within the western imperialist discourses, the very nature of gameplay itself challenges these set notions – in a way remediating the ambiguity and anxieties of the representations of empire and its spatial constructs in earlier media.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Video Games and Slavery - Mukherjee, Souvik (Transactions of the Digital Games Research Association, 2016)
What are the implications of freedom and agency when a player exercises agency to prevent another player or a non-player character fromacting freely? Such a scenario, taken to an extreme, would be that of slavery and in turn, would raise questions about the nature of freedom itself. Video games have recently begun to address questions of slavery in earnest although academic discussions on games have not yet caught up: the presence of slavers in Fallout 3, the portrayal of racism in Bioshock Infinite (Irrational Games 2014) and the direct depiction of the Caribbean slave trade in Assassin’s Creed: Freedom Cry (Ubisoft 2013) are extremely appropriate cases in point. This article compares the representation of slavery in video games to that of slave narratives in earlier media in order to examine how effectively digital games are able to convey the horrors of slavery as a human condition and what they can teach about the notion of human freedom and agency per se.
Number: 3
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Playing Subaltern: Video Games and Postcolonialism - Mukherjee, Souvik (Games and Culture, 2018)
The postcolonial has still remained on the margins of Game Studies, which has now incorporated at length, contemporary debates of race, gender, and other areas that challenge the canon. It is difficult to believe, however, that it has not defined the way in which video games are perceived; the effect, it can be argued, is subtle. For the millions of Indians playing games such as Empire: Total War or East India Company, their encounter with colonial history is direct and unavoidable, especially given the pervasiveness of postcolonial reactions in everything from academia to day-to-day conversation around them. The ways in which games construct conceptions of spatiality, political systems, ethics, and society are often deeply imbued with a notion of the colonial and therefore also with the questioning of colonialism. This article aims to examine the complexities that the postcolonial undertones in video games bring to the ways in which we read them.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Crab-Rangoons in Kyrat: (Re)Writing South-Asian History in Far Cry 4 - Mukherjee, Souvik (Games and Culture, 2021)
Recent research has started focusing on the representation of history in videogames. Such representation is almost always of mainstream history and usually presented from a Western perspective. Set in a fictitious Himalayan kingdom in South Asia, Ubisoft’s Far Cry 4 is arguably a crucial example of how history is represented using Western and even colonial frameworks and where the narratives that do not emerge from conventional written history are almost always rendered invisible. Using the frameworks of Subaltern Studies and “border-thinking,” this essay attempts to unpack issues of Orientalism and “colonial difference”; it then engages with postcolonial digital humanities and postcolonial game studies to comment on how history is represented in videogames and how the neglected gaps and silences in the game are important in constructing the historiography in videogames. In the process, the essay engages in a debate with current notions of videogame-historiography.
Keywords: 1-Jeux vidéo; 2-Histoire/Historiographie critique; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Games Studies India Adda #5: Souvik Mukherjee - Game Studies India Adda (Game Studies India Adda, 2021)
Speaking to the 'Missing' Player: Subaltern Poetics in Indian Videogames The degree of interactivity and agency of the player-character in videogames is often a moot question in Games Studies discourses (Atkins 2002 , Juul 2004, Salen and Zimmerman 2001). The assumption is that whether illusory or real, agency is an important element that drives the plot of digital games. To assume this, however, is to argue from a position of privilege and some videogames use their in-game mechanics to emphasise this. The assumption of a selfhood by the player while playing a digital game is the precondition to the experience of agency. Such a precondition is hardcoded into the gameplay on the basis of a default notion of empowerment and entitlement. What happens, however, in the case of the character that does not provide this sense of agency or for the game wherein such an experience of selfhood may not be possible? Using a well-worn but very relevant term from Postcolonial discourses, one could ask what happens where the game is about the Subaltern. Considering videogame studies from non-Western and South-South perspectives, such a default assumption of selfhood or agency may be challenged. Elsewhere (Mukherjee 2017), I have cited examples from the Cameroon, Indonesia and India that begin to address this challenge. Here, I wish to take two games from India as my texts for close-reading (or close-play) and show how a different poetics operates; indeed, my primary objective is to enquire into how the videogame as a narrative medium, which is by default apparently premised on agency, functions for the subaltern.
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Introduction to the Special Issue on Postcolonial Perspectives in Game Studies - Mukherjee, Souvik; Hammar, Emil Lundedal (Open Library of Humanities, 2018)
The treatment of colonialism in video games, barring a few notable exceptions, is marked by a Western and, specifically, late 19th-century imperialist bias. Simultaneously, in the past two decades of multifaceted research and the development of robust theoretical frameworks in the still fledgling discipline of game studies, postcolonial discourses, whether they comprise critiques of imperialism or neocolonialism, have not been prominently highlighted until very recently. A coherent effort to bring together the current research on postcolonialism in video games was also urgently required. Further, the past years has seen a rather persistent, albeit unexpected, emergence of a pro-colonial or pro-imperialist discourse in mainstream academia that even justifies the continuance of empire as an ameliorating influence on the people of the so-called developing countries, most of which had formerly been colonized by European powers.Thus, it is the aim of this issue to address this epistemic omission and counter such bias where it exists by also bridging video games research with larger discussions of postcolonialism in other humanities contexts and disciplines. The various articles in this special issue offer a range of perspectives from epistemological power to theory and praxis in critical academia, to contexts of production and practices of play, to close readings of postcolonial traces in video games. These varying approaches to the analysis of video games and their societal and historical contexts open up the debates further to a diverse set of topics ranging from board games to phone games or from mainstream high-budget console games to indie titles that question colonialism. As video games address issues relating to orientalism, subalternity, and hybridity as well as the current ambiguities in conceiving nationhood and the postcolony, the articles in this issue will also likely adumbrate further serious commentary that will develop both game studies research and current conceptions of the postcolonial.
Number: 2
Keywords: 1-Jeux vidéo; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Egoshooting in Chernobyl: Identity and Subject(s) in the S.T.A.L.K.E.R. Games - Mukherjee, Souvik (Computer Games and New Media Cultures: a Handbook of Digital Games Studies, 2012)
The issue of identity formation when playing an avatar in a video game has recently become perceived as both increasingly complex and contentious. Game critics argue both for and against the apparent seamlessness in the identity formation in video games. However, while the case against seamlessness builds up with respect to other gaming genres, first-person shooters (FPS) are often still singled out as best representing this first-person identification whereby players were supposed to be totally immersed in their avatars while they played the game. In the light of recent research, this chapter builds on earlier research to reveal further problems in assuming a seamless merging of identity even in the FPS. It argues that the very conception of subjectivity has always been problematized through the FPS, and that the genre itself self-consciously keeps pointing this out. As an example of the latter, the chapter focuses on the S.T.A.L.K.E.R. video games to show how FPS games prompt players to question their in-game identity(ies) because the playing subject, instead of being a fixed entity, is hard-wired into the process of exploration that constitutes gameplay.
Keywords: 1-Jeux vidéo; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

Videogame Wastelands as (Non- )Places and 'Any-Space-Whatevers' - Mukherjee, Souvik (Ludotopia: Spaces, Places and Territories in Computer Games., 2019)
Where do computer games "happen"? The articles collected in this pioneering volume explore the categories of "space", "place" and "territory" featuring in most general theories of space to lay the groundwork for the study of spatiality in games. Shifting the focus away from earlier debates on, e.g., the narrative nature of games, this collection proposes, instead, that thorough attention be given to the tension between experienced spaces and narrated places as well as to the mapping of both of these.
OCLC: 1119630732
Keywords: 1-Jeux vidéo; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé

First Person Encounters #5: Abhi, creator of Venba - Game Studies India Adda
Venba is a narrative cooking game, where you play as an Indian mom, who immigrates to Canada with her family in the 1980s. Players will cook various dishes and restore lost recipes, hold branching conversations and explore in this story about family, love, loss and more. More on Steam: https://store.steampowered.com/app/14.... Developer, Abhi, gives Game Studies India an exclusive preview talking about identity, nostalgia, memory and of course, food. In conversation with Poonam Chowdhury and Souvik Mukherjee.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Créateur.rice PANDC; 5-Identités diasporiques; _Nettoyé

First Person Encounters #1: A Game Studies India Adda Podcast - Game Studies India Adda (2020)
The First Podcast in a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude de la réception; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

First-Person Encounters #4: Poornima Seetharaman - Game Studies India Adda (Game Studies India Adda, 2021)
First Person Encounters is a series of podcasts presented by Games Studies India, about our first experiences with Games while growing up in India. This our third podcast where we talk with Poornima Seetharaman. She is the first Indian to be inducted in the Women in Games (WIGJ) Hall of Fame and is also the lead game designer at Zynga. Hear as we talk about her foray in the world of gaming.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Asie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; _Nettoyé

Politics of Production: Videogames 10 years after Games of Empire - Hammar, Emil L.; de Wildt, Lars; Mukherjee, Souvik; Pelletier, Caroline (Games and Culture, 2021)
2019 marked ten years since the publication of Nick Dyer-Witheford and Greig de Peuter’s Games of Empire, which has become a seminal book in videogame cultural criticism. Ten years later, there is still a pressing need for cultural and materialist criticism of the politics of production within game studies. In putting together this special issue, our hope is to identify new developments in the game industry and academia that are emblematic of 21st-century capitalism. Just as Games of Empire popularised critical political-economic perspectives ten years ago, we encourage others, as the authors in this issue did, to continue and maintain investigations into questions of ownership, privatized property, coercive class relations, military operations and radical struggle. Such analyses are necessary not only to trace but also to open up new directions in game culture and academia for decades to come.
Keywords: 1-Jeux vidéo; 2-Étude des industries culturelles; 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé

Round Table Discussion on Nation(alism), Identity and Video Gaming with Megan Condis, Marijam Didzgalvyt , Georg Hobmeier and Souvik Mukherjee - Trattner, Kathrin; Condis, Megan; Didzgalvyt, Marijam; Hobmeier, Georg; Mukherjee, Souvik; Kienzl, Lisa (Gamevironments, 2019)
Questions of nation and identity not only concern multiple aspects of video games, their production, and their consumption, but also require further and manifold discussion from different perspectives. In an effort to bring together voices from different fields that engage with video games and gaming practices from various perspectives, this virtual round table discussion attempts to open up the conversation beyond the realms of academia. Kathrin Trattner and Lisa Kienzl talked to Megan Condis, Marijam Didzgalvyt , Georg Hobmeier and Souvik Mukherjee about how concepts such as nation(alism) and identity impact video game representations, the gaming industry, and online gaming cultures in numerous ways.
Accepted: 2020-03-25T23:30:29Z
Keywords: 1-Jeux vidéo; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; _Nettoyé